Using Teacher – Made Videos in Learning Speaking - Maharatul Prismulanda; Witri Oktavia (Universitas Negeri Padang, 2023)
Speaking is one of the important skills in learning English. Teacher - made videos are the right method for learning in this digital age, with teachers being able to make videos according to the abilities of their students. The purpose of this study was to investigate what the sixth-grade SMP Muhammadiyah students in Padang thought about using videos made by teachers to teach speaking. SMP Muhammadiyah 6 Padang students contributed to the study's population. The population consisted of 128 students, class VIII 1 was selected to be the sample in this study through the cluster random sampling method. Two sessions were held for conducting this research, and two videos were made accessible. Researchers used a questionnaire with two indicators—perceived effectiveness and perceived interest—to collect data. Students at SMP Muhammadiyah 6 Padang feel that using teacher-produced videos helps them recognize the lessons and increases their interest in learning to speak English, which means the result in this study is very positive perspective.